2023
DOI: 10.3390/cells12202458
|View full text |Cite
|
Sign up to set email alerts
|

Limbal Epithelial Stem Cells in the Diabetic Cornea

Lamia Nureen,
Nick Di Girolamo

Abstract: Continuous replenishment of the corneal epithelium is pivotal for maintaining optical transparency and achieving optimal visual perception. This dynamic process is driven by limbal epithelial stem cells (LESCs) located at the junction between the cornea and conjunctiva, which is otherwise known as the limbus. In patients afflicted with diabetes, hyperglycemia-induced impairments in corneal epithelial regeneration results in persistent epithelial and other defects on the ocular surface, termed diabetic keratopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 116 publications
1
9
0
Order By: Relevance
“…Microarray analysis demonstrated that among the 29 miRNA studied, miR-146a, 21, and 424 were the most upregulated, while miR-509-3p and 143 were expressed at the lowest level. This is in line with other reports, which indicate that overexpression of miR-146a in the diabetic limbus may result in a reduced corneal inflammatory and healing response [ 24 , 93 , 94 ]. In another study, genome-wide sequencing was applied, identifying differences in expression profiles of 20 miRNA between normal and diabetic human corneas [ 95 ].…”
Section: The Role Of Insulin and Effect Of Diabetessupporting
confidence: 93%
See 4 more Smart Citations
“…Microarray analysis demonstrated that among the 29 miRNA studied, miR-146a, 21, and 424 were the most upregulated, while miR-509-3p and 143 were expressed at the lowest level. This is in line with other reports, which indicate that overexpression of miR-146a in the diabetic limbus may result in a reduced corneal inflammatory and healing response [ 24 , 93 , 94 ]. In another study, genome-wide sequencing was applied, identifying differences in expression profiles of 20 miRNA between normal and diabetic human corneas [ 95 ].…”
Section: The Role Of Insulin and Effect Of Diabetessupporting
confidence: 93%
“…A fundamentally negative impact of diabetes on the corneal epithelium is closely linked to its effect on LESC functioning [ 24 ]. A significant reduction in Palisades of Vogt in all four limbus quadrants was demonstrated in patients with type 2 diabetes using in vivo confocal microscopy [ 65 ].…”
Section: The Role Of Insulin and Effect Of Diabetesmentioning
confidence: 99%
See 3 more Smart Citations